The MADS-box genes SOC1 and AGL24 antagonize XAL2 functions in Arabidopsis thaliana root development - Castañón-Suárez, Claudio A.; Arrizubieta, Maite; Castelán-Muñoz, Natalia; Sánchez-Rodríguez, Diana Belén; Caballero-Cordero, Carolina; Zluhan-Martínez, Estephania; Patiño-Olvera, Sandra C.; Arciniega-González, J.Arturo; García-Ponce, Berenice; Sánchez, María de la Paz; Álvarez-Buylla, Elena R.; Garay-Arroyo, Adriana (Frontiers in Plant Science, 2024)
MADS-domain transcription factors play pivotal roles in numerous developmental processes in Arabidopsis thaliana. While their involvement in flowering transition and floral development has been extensively examined, their functions in root development remain relatively unexplored. Here, we explored the function and genetic interaction of three MADS-box genes (XAL2, SOC1 and AGL24) in primary root development. Our findings revealed that SOC1 and AGL24, both critical components in flowering transition, redundantly act as repressors of primary root growth as the loss of function of either SOC1 or AGL24 partially recovers the primary root growth, meristem cell number, cell production rate, and the length of fully elongated cells of the short-root mutant xal2-2. Furthermore, we observed that the simultaneous overexpression of AGL24 and SOC1 leads to short-root phenotypes, affecting meristem cell number, cell production rate, fully elongated cell size, but only the overexpression of SOC1 affects distal root stem cell differentiation. Additionally, these genes exhibit distinct modes of transcriptional regulation in roots compared to what has been previously reported for aerial tissues. Moreover, our findings revealed that the expression of certain genes involved in cell differentiation, as well as stress responses, which are either upregulated or downregulated in the xal2-2 mutant, reverted to WT levels in the absence of SOC1 or AGL24